(untitled) (Journal of Sciences & Technology, 2017)
Physical concept has been applied to space observation by using images and data of LANDASAT 7 in order to to extract quantitative information about the studied areas facilitate . The final product should respect a norm in presenting a list of physical indicators or minimal reference classes.